Investigation of Pharmacokinetics, Molecular Docking, and Dynamics of Xanthomicrol-Derived Compounds Against Various Mutated Proteins in Lung Cancer Cells - Kurniawan, Muhammad Akbar S; Baari, Muhamad Jalil; Sabila, Laili Cahyani; Amin, Rana Triana (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Lung cancer remains one of the leading causes of global mortality, primarily due to drug resistance and the adverse effects of conventional therapies. Therefore, the discovery of novel compounds that are both effective and safe is crucial for the development of alternative treatments. This study employed a computational approach to evaluate the therapeutic potential of Xanthomicrol-derived compounds targeting mutated proteins commonly associated with lung cancer. Four derivatives (u1a, u2a, u3a, and u4a) were assessed using pharmacokinetic (ADMET) predictions, molecular docking, and molecular dynamics simulations against ten mutated lung cancer-related proteins (1nq1, 1x2j, 4b3z, 4j97, 5l2q, 6pwa, 6usx, 7pgk, 7pgl, and 7r7k). ADMET predictions revealed that all compounds had good gastrointestinal absorption, did not cross the blood–brain barrier, and exhibited favourable safety profiles. Among them, compound u3a showed the highest binding affinity toward seven mutated proteins, with docking scores ranging from -5.9 to -9.4 kcal/mol. Molecular dynamics simulations further supported the stability of u3a protein interactions, indicated by low RMSF values and an optimal radius of gyration. These results suggest that u3a is a promising candidate for targeted lung cancer therapy and warrants further experimental validation.